Tuberculosis infection control in rural South Africa: survey of knowledge, attitude and practice in hospital staff. - Kanjee, Z; Catterick, K; Moll, A P; Amico, K R; Friedland, G H (The Journal of hospital infection, 2011)
A baseline assessment of tuberculosis infection control (TB IC) knowledge, attitude and practice (KAP) was conducted among staff in a resource-limited rural South African hospital where nosocomially transmitted multi- and extensively drug-resistant (M/XDR) TB had been reported. Assessment consisted of anonymous questionnaires and direct observation during July-September 2007, soon after the report of M/XDR-TB. Data were obtained from 57 questionnaires and 10h of direct observation. While knowledge and attitudes were generally supportive of TB IC implementation, 49.1% of staff felt that the hospital did not care about them and/or was not working to prevent staff TB infections, and 42.9% were less willing to continue as a healthcare worker because of staff TB/MDR-TB/XDR-TB deaths. Practices were variable. The recent appointment of an IC officer and implementation of natural ventilation were strengths, but the facility lacked a TB IC policy, the patient TB screening process was inadequate, and 41.5% of respondents were unaware of their personal human immunodeficiency virus (HIV) status. Respondents reported a number of barriers to TB IC implementation such as concerns about the confidentiality of staff health information, the stigma of TB and HIV, inadequate resources, and patient non-compliance. Assessment of staff KAP provided useful data regarding deficits and barriers to TB IC, and helped to focus subsequent IC strategies. Given the critical importance of reducing nosocomial TB transmission, it is recommended that facilities should conduct simplified TB IC assessment, ensure the confidentiality of staff health information, address the stigma of TB/HIV, and implement multi-faceted TB IC facility and behavioural change interventions. Behavioural science methods have the potential to improve TB IC research and implementation.
Keywords: Attitude of Health Personnel; Cross Infection; Female; Health Knowledge, Attitudes, Practice; Health Personnel; Hospitals; Humans; Infection Control; Male; Professional Competence; Questionnaires; Rural Population; South Africa; Tuberculosis